Studi Historiografi Islam Klasik: Kritik dan Tinjauan Terhadap Karya Al-Mas’udi - Darmawan, Budi; Chaniago, Danil Mahmud (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2024)
This study critically evaluates and analyzes the historical writings of al-Mas'udi, focusing on his influence on historical writings in the classical Islamic era. The author is interested in examining al-Mas'udi's contributions in his works, particularly on Islamic historiography from the classical period. The researcher uses an approach that is considered appropriate for this study, namely a qualitative approach using analytical descriptive techniques and assisted by literature review. The purpose of this article is to provide an assessment and critical analysis of al-Mas'udi's influence on historical writing in the classical Islamic era, with a particular focus on his bibliography and writing techniques or methods. And through his travels and research, played a major role in Classical Islamic historiography with his major works. Although criticized for its consistency and the dirayah method used, his work remains valuable as a source of knowledge about Islamic history and geography. Al-Mas'udi's Muktazilah influence has also created his distinguishing thematic approach, which reflects the general Muslim worldview of his time. The evolution of history writing in Islam is reflected in the shift from the historical method to the dirayah method, which emphasizes direct experience and factors influencing historical events used by Al-Mas'udi.